SHORT-COGNITIVE BEHAVIOUR TREATMENT: A PREVENTIVE MEASURE FOR ADOLESCENTS’ EMOTIONAL DISTRESS - Sylvester Ezechinyere Eze, Sussan Olufunmilola Adeusi, Gboyega Emmanuel Abikoye (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2024)
Over the last two decades, there has been a significant increase in the number of adolescents suffering from mental health conditions, predominantly depression, anxiety, and stress, in low-income rural communities. These communities face challenges such as a lack of mental health professionals, low treatment rates, and a paucity of studies on therapeutic interventions. This study investigated the efficacy of short-cognitive behaviour treatment (S-CBT) aimed at reducing emotional distress symptoms using a pre-test, post-test control group experimental design. Forty-eight participants with a mean age of 13.38 years (SD =1.8) were randomly selected from four mixed high schools in Oyo town and assigned into two equal groups of 24 treatment and no-treatment participants by ballot. Emotional distress symptoms were measured at pre-test, post-test, and post-intervention using the 21-item version of the Depression, Anxiety, and Stress Scale (DASS21). Data were analysed using a paired sample t-test. Results showed that a 50-minute session per week for six sessions, exposing treatment group participants to S-CBT with psychoeducation, cognitive restructuring, breathing relaxation, and affirmation of self-positive skills as components, was significantly effective at reducing elevated emotional distress symptoms (t (20) =6.93, p < 0.001). The mean difference showed that the treatment effect remained after four weeks (M =30.35) when compared to pre-test (M =56.85) and post-test (M = 26.24) scores of participants in the treatment group (t (13) =6.90, p < 0.01). Additionally, there was no significant difference in elevated symptoms at pre-test (M = 49.30) and post-test (M =48.35) measures of emotional distress among control group participants (t (19) =0.14, p > 0.05). The results indicated that administering S-CBT sessions in schools can ameliorate the incidence of emotional distress and associated negative mental health consequences. Further studies are encouraged to explore the viability of S-CBT considering the highlighted treatment components.